An Agile Radio Framework for Unmanaged Wireless Environments - Wang, Zhou; Chandra, Ranveer; Moscibroda, Thomas; Gefflaut, Alain; de Baynast, Alexandre; Bahl, Victor (MobiHoc '09 Proceedings of the tenth ACM international symposium on Mobile ad hoc networking and computing, New Orleans, LA, USA, 2009)
The proposed demonstration is based on commodity 802.11 wireless cards and a low cost 2.4GHz sniffing device and shows how current WLAN based networks can benefit from spectrum awareness and dynamic access to the assigned band. The demonstrator presents a solution to problems in current wireless networks, like inefficient radio spectrum usage and limited ability to withstand interferences. The presented spectrum-aware radio management framework flexibly negotiates transmission parameters based on spectrum usage and application requirements and opportunistically utilizes available bandwidth. A key feature of this demonstrator is the fact that it breaks the traditional fixed channel bandwidth limitation and enables dynamic bandwidth allocation according to the needs of applications. It continuously monitors the assigned spectrum, tracks application behaviour, and dynamically adapts to the radio environment, such as interference and competition. Furthermore, a cross-media roaming mechanism is provided in the framework to support seamless handovers within and between radio technologies. Our enhancements are transparent to upper layer applications and will automatically benefit any software using network resources. The presented demonstrator uses wireless video streaming in a typical household scenario to illustrate the benefits without changes to the multimedia applications.
Pages 333-334. Accepted as demo.